Bioethical principles of R&D&i in the university environment : a literature review - Vidarte-Llaja, Annie Mariella (2024)
The objective of this study is to identify the bioethical principles that are applied in research, development and innovation (R+D+I) activities in the university environment, mainly considering the areas of engineering knowledge. For this purpose, a systematic mapping of the literature (SLM) was carried out, using four digital databases and three research questions: (i) what are the bioethical principles considered in R+D+I in the university setting? (ii) what are the main contributions to R&D&i in the university environment? and, (iii) what application domains do R&D&i cover in the university environment? In the MSL, 1081 articles were obtained from the databases, in the period 2000-2022, and then 34 primary studies were selected. Of the primary studies, 38% refer to the application of bioethical principles in research, from the perspectives of UNESCO, biomedical practice, principlism and scientific integrity. It is concluded that, in the university environment various bioethical principles are applied that, based on various approaches, can be associated with the bioethical currents of personalism and principlism.